Spanish consensus on treat to target for osteoporosis. Issue 2 (February 2018) - Nogués, X.; Nolla, J.; Casado, E.; Jódar, E.; Muñoz-Torres, M.; Quesada-Gómez, J.; Canals, L.; Balcells, M.; Lizán, L.
Abstract Summary To reach a Spanish expert consensus on a treat-to-target strategy in osteoporosis, a Delphi Consensus Study has been developed. Most of the experts (59.8%) were rheumatologist with a mean clinical experience of 21.3 years (SD 8.5). Consensus was achieved for 70% of the items. Therapeutic objectives, patient follow-up scheme, treatment failure criteria, and appropriate treatment choice for use in T2T strategy in Spain have been defined. Introduction The paper aims to achieve a Spanish expert consensus on a treat-to-target (T2T) strategy in osteoporosis. Methods A scientific committee led the project and was involved in expert panel identification and Delphi questionnaire development. Two Delphi rounds were completed. The first-round questionnaire included 24 items and assessed, using a seven-point Likert scale, the experts' wish (W) and prognosis (P) in 5 years for each topic (applicability, therapeutic objectives, patient follow-up, and possible treatment to be prescribed). Items for which there was no consensus in the first round were included in the second round. Consensus was defined as ≥75% agreement (somewhat/mostly/entirely agree) or disagreement (somewhat/mostly/entirely disagree) responses. Results Of the experts, 112 and 106 completed the first and second rounds, respectively. 59.8% were rheumatologists with a mean clinical experience of 21.3 years (SD 8.5). Consensus was achieved for 70% of the items, and was established regarding the utility of a T2T strategy to define therapeutic objectives, optimal follow-up, and therapeutic algorithm. Participants agreed on the utility of the bone mineral density (BMD) value (T-score >−2.5 SD for spine and >−2.5/−2.0 SD for femoral neck), lack of fractures, and fracture risk (FRAX) as therapeutic objectives. For measuring BMD changes, consensus was achieved on the suitability of hip and femoral neck locations. Experts agreed to consider treatment failure as when a significant BMD gain could not be achieved, or when a new fracture occurs within 2–3 years. There was consensus that all proposed therapies should achieve a therapeutic target through T2T strategy (treatments with the highest consensus scores were denosumab and teriparatide). Conclusion The therapeutic objectives, patient follow-up scheme, treatment failure criteria, and appropriate treatment choice for use in T2T strategy in Spain have been established by a panel of experts. Some aspects nevertheless still require further analysis.